Removal of aqueous Congo red and malachite green using ackee apple seed–bentonite composite - Adebayo, Matthew A.; Adebomi, Joshua I.; Abe, Taiwo O.; Areo, Felicia I. (Colloid and interface science communications, 2020)
The efficiency of a composite prepared from bentonite and ackee apple seed (CBAAS) to remove Congo red and malachite green from aqueous solutions was explored. The CBAAS was characterised using Scanning Electron Microscopy, Fourier Transform Infrared spectroscopy, X-ray diffraction, and porosimetry techniques. Batch adsorption method was used to assess the variations of pH of the medium, contact time, temperature and initial concentrations of Congo red and malachite green. Kinetic and equilibrium data were properly described by general order kinetic and Liu model, respectively. The maximum adsorption capacities obtained from the Liu model are 1439.9 mg g−1 and 706.72 mg g−1 for Congo red and malachite green, respectively. Adsorption of the two dyes was spontaneous and exothermic. Acetone was able to desorb the two dyes from the surface of CBAAS. The CBAAS could serve as an alternative adsorbent for treatment of contaminated water that contains Congo red and malachite green. [Display omitted] •An adsorbent for efficient removal of Congo red and Malachite green was produced from Ackee apple seed and bentonite.•Maximum adsorption capacities obtained for Congo red and Malachite green are 1439.9 and 706.72 mg g−1, respectively.•The adsorbent showed excellent performances for treatment of dye-house simulated wastewaters.•Dye-loaded adsorbents were regenerated using acetone and reused up to six times.